Konsep Manusia Sempurna Perspektif Ibnu Miskawaih (Telaah Buku Tahdzib Al-Akhlak) - Almunawaroh, Andini Tiara (Jurnal Riset Agama, 2022)
Ibn Miskawaih in Tahdzib al-Akhlak spoke for the existence of humans as a creature that can achieve perfection. This study aims to describe the thought of the human philosophy of Ibn Miskawaih. This research uses a qualitative approach with a descriptive method of analysis based on literature study techniques (library research). As for the findings of this study, that humans according to Ibn Miskawaih consisted of three kinds of power, namely lust (syahwiyah), anger/brave (ghodbiyah) and thinking power (nathiqah). Humans will be perfect human if they are able to develop their thinking power. And to achieve human perfection must use as much as possible and practical power.